Green growth - John Zysman; Mark Huberty; Arno Behrens; Bert Colijn; Richard S. J. Tol; Jorge Nú\~nez Ferrer; Michel Aglietta; Jean-Charles Hourcade (Intereconomics, 2012)
Green growth is now a central theme of the international climate change negotiations. The Rio+20 Conference in June will concentrate on green growth as one of its main priorities. The Europe 2020 strategy has identified green growth as a fundamental pillar of EU economic policy. This Forum takes stock of the academic discussion and examines the theoretical and empirical underpinning of the concepts of green growth and employment through environmental policy.
Keywords: 330; Wirtschaftswachstum; Nachhaltige Entwicklung; Systemtransformation; Makroökonomischer Einfluss; Wirtschaftliche Anpassung; Europa